Impact Response of Different Classes of Fibre Reinforced Concrete - Vivas, Juan Carlos (2021)
The use of fibre reinforced concrete in structural elements exposed to impacts or different types of extreme loading represents one of the main fields of application of this high-performance material. Nevertheless, there is not a general consensus about a test for impact characterization of fibre concretes and, specifically a procedure to evaluate the contribution of fibres after cracking. It is well known that fibres control the evolution of cracks, improving the durability of concrete elements. Nowadays there are many structural fibres available; one of the greatest advantages to enhance the use of different fibres is the introduction of FRC classes in the fib Model Code 2010. However, there are not references about the relationship between the residual capacity measured in static tests (i.e. EN 14651) and the impact response. A drop weight impact test method is proposed to evaluate the contribution of different fibres considering both the cracking resistance and the behaviour in cracked state. Results of FRC belonging to different classes, incorporating different contents of steel, glass and polymer macrofibres are presented and compared. The effect of the residual capacity measured on standard bending tests on the impact resistance is discussed.